2009
DOI: 10.1021/nl901869j
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Swimming Properties of Artificial Bacterial Flagella

Abstract: Artificial bacterial flagella (ABFs) consist of helical tails resembling natural flagella fabricated by the self-scrolling of helical nanobelts and soft-magnetic heads composed of Cr/Ni/Au stacked thin films. ABFs are controlled wirelessly using a low-strength rotating magnetic field. Self-propelled devices such as these are of interest for in vitro and in vivo biomedical applications. Swimming tests of ABFs show a linear relationship between the frequency of the applied field and the translational velocity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
413
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 455 publications
(430 citation statements)
references
References 28 publications
14
413
1
2
Order By: Relevance
“…One of the leading avenues of such research has been in the use of magnetic fields to actuate artificial bioinspired helical structures in fluids. [19][20][21][22] Alternatively, a number of studies have focused on the collective behavior of bacteria swarm, both experimentally [23][24][25][26][27] and theoretically. 23,[28][29][30][31][32] Investigations have shown that bacterial suspensions develop transient patterns of coherent locomotion with correlation lengths much larger than the size of individual organisms.…”
Section: Introductionmentioning
confidence: 99%
“…One of the leading avenues of such research has been in the use of magnetic fields to actuate artificial bioinspired helical structures in fluids. [19][20][21][22] Alternatively, a number of studies have focused on the collective behavior of bacteria swarm, both experimentally [23][24][25][26][27] and theoretically. 23,[28][29][30][31][32] Investigations have shown that bacterial suspensions develop transient patterns of coherent locomotion with correlation lengths much larger than the size of individual organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The microrobot is steered in the horizontal plane by a uniform magnetic field. As for helical swimmers actuated by a rotating magnetic field, researchers estimate the rotation direction of the field; for example, a rotating magnetic field with a fixed rotation axis to actuate the helical swimmer to follow a straight line [36,40,73]. Then, Ghosh et al [37] achieved following a curved trajectory (e.g., "R@H") with their helical microrobots, which were navigated by a pre-programmed controller to actuate the magnetic field.…”
Section: Open-loop Controlmentioning
confidence: 99%
“…More specifically, the bubble type (putt-putt boat type) swimmers are using momentum transfer through the microstreaming formed by bubble oscillation [19,20]. The micro robots that harness natural organisms or use the artificial cilia/flagella (regardless of motion types, corkscrew motion, or flexible oar motion) generate propulsion via viscous stress interaction [17,18,[21][22][23][24][25][26]. Among the chemical micro swimmers, even though there are still debates on the mechanism [27], some devices utilize the bubble recoiling method to make momentum transfer by inertia propulsion [28][29][30][31].…”
Section: Propulsion In Micron and Nano Scalementioning
confidence: 99%
“…Leoni et al [40] first realized this model experimentally with optical tweezers and compared the experimental results with the numerical solution. [19], 1′-acoustic scallop (Re is based on oscillating speed and amplitude), 2-oscillating micro bubble (Re is based on body speed and size) [20], 2′-oscillating micro bubble (Re is based on oscillating speed and amplitude), 3-artificial magnetic bacteria flagella [21], 4-artificial magnetic nanostructured propeller [22], 5-magnetically actuated colloidal [23], 6-magnetotactic bacteria propeller [24], 7-flagella-based propulsion [25] [17], and 19-Escherichia coli [18]. Note that the triangles denote inertia dominant propulsion, the squares denote viscous dominant propulsion, and the circles means the propulsion mechanisms cannot be clearly classified.…”
Section: Propulsion By Irreversible Strokesmentioning
confidence: 99%
See 1 more Smart Citation